Facile Fabrication of SrTiO3@MoS2 Composite Nanofibers for Excellent Photodetector Application - Jinghong Li; Lun Zhang; Di Wang; Ran Wang; Xiujuan Liu; Jingxin Zhou (Journal of Chemistry)
Molybdenum disulfide (MoS2), as a kind of transition metal dichalcogenide, has been widely studied for its excellent compatibility with most of inorganic nanomaterials. Nevertheless, its microscale and agglomeration limit the performance severely. Therefore, the special structure of V-MoS2 has drawn a lot of interest, which can not only reduce the size of MoS2 nanosheets but also improve the valence electron structure of the materials. In this work, SrTiO3@MoS2 composite nanofibers were synthesized by the simple electrospinning and hydrothermal method, and it was applied as a novel material for photodetector. SEM, TEM, EDX, XRD, I-T curves, and EIS analysis were used to study the structure and properties of the prepared SrTiO3@MoS2 composite nanofibers. Simulating under sunlight at a potential of 1.23 V, the prepared composite materials exhibited a superior photoelectric performance of photocurrent density of 21.4 μA and a resistance of 2.3 Ω. These results indicate that the composite of SrTiO3 nanofiber adhered with V-MoS2 has a stable composite structure, good electrical conductivity, and photoelectric sensitivity and is a suitable material for photodetectors. This work provides new ideas for the preparation of self-assembled materials and their application in photodetectors.